PENGARUH KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PELANGGAN (STUDI PADA KEDAI KOPI DOESOEN COFFEE & SPACE) - Triatama, Aklas Nurdika; Hatono, Hartono; Nugeraha, Prasetya (Jurnal Kompetitif Bisnis, 2023)
This“study purposed to determine the magnitude of the“effect“ of“ service quality on increasing customer“satisfaction at a coffee shop. Doesoen Coffee & Space. Explanatory Research is the type of Research used, and consumers of Doesoen Coffee & Space coffee shops are the population in this study. The sampling“technique in“this“study was purposive“sampling“ with a sample of 100 people.” Based on data“analysis. research and data analysis, service quality with dimensions, responsiveness, “assurance, empathy, and tangibles have a “and“significant effect on customer satisfaction; This shows that the ’influence’ of service quality with dimensions, responsiveness, guarantee, empathy, and form ’can significantly increase customer satisfaction at Doesoen Coffee & Space’s coffee shop”.